Clinical and urodynamic studies in 100 elderly incontinent patients. - Castleden, C M (1981)
Clinical details were noted and urodynamic studies carried out on 100 elderly patients referred to an incontinence clinic, of whom 48 attended as day patients. Thirty patients had no problem apart from their incontinence, and only 38 had a clinically detectable neurological lesion. The average mental orientation score in 48 of the patients was 7.6, 23 patients scoring the top score of 10. Most patients were mobile without assistance from another person. Patients could be placed into one of four diagnostic groups according to the appearance of the cystometric tracings, but no bladder capacity or pressure was characteristic of any group. The maximum urethral closure pressure and functional profile length were similar for each group within each sex. There was no correlation between clinical and urodynamic findings, yet each of the four diagnostic categories have different therapeutic implications. It is concluded that urodynamic investigation is necessary in elderly incontinent patients before treatment.